1979
DOI: 10.1246/bcsj.52.2755
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction Study of Aqueous Ionic Solutions. I. Aqueous Solutions of Lithium Chloride and Caesium Chloride

Abstract: The structure factors Sm(Q) for aqueous solutions of LiCl and CsCl at room temperature, including those for heavy water, have been determined by means of the time-of-flight (TOF) neutron diffraction method using an electron linear accelerator (LINAC). Analysis of the diffraction data has been carried out for the aqueous ionic solutions as well as for pure heavy water. The following results were obtained with respect to the structure of the nearest hydration shell: (a) the coordination numbers are 4 for Li+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 18 publications
9
38
0
Order By: Relevance
“…LiCl, LiBr and Lil are very hygroscopic and form highly concentrated aqueous solutions, which are easily supercooled and vitrified. At ambient temperature, many investigations on these solutions have been performed using X-ray [1 -7] and neutron [8][9][10][11][12][13][14][15][16] diffraction, and computer simulation [17][18][19][20] methods. These investigations have revealed that (i) the distances of Li + -0 and Li + -H(D) are 2.0 and 2.6 Ä, respectively, with hydration numbers of four to six, depending on the salt concentration, (ii) that the coordination geometry of the water molecules in the first hydration shell of Li + is nearly tetrahedral in highly concentrated solutions, (iii) the distance X~-0(H 2 0) is 3.1, 3.3, and 3.6 Ä for CP, Br", and I -, respectively, with hydration numbers of about six, (iv) water molecules approach Li + with their dipole axis, while the X -ion with their O-H bond axis.…”
Section: Introductionmentioning
confidence: 99%
“…LiCl, LiBr and Lil are very hygroscopic and form highly concentrated aqueous solutions, which are easily supercooled and vitrified. At ambient temperature, many investigations on these solutions have been performed using X-ray [1 -7] and neutron [8][9][10][11][12][13][14][15][16] diffraction, and computer simulation [17][18][19][20] methods. These investigations have revealed that (i) the distances of Li + -0 and Li + -H(D) are 2.0 and 2.6 Ä, respectively, with hydration numbers of four to six, depending on the salt concentration, (ii) that the coordination geometry of the water molecules in the first hydration shell of Li + is nearly tetrahedral in highly concentrated solutions, (iii) the distance X~-0(H 2 0) is 3.1, 3.3, and 3.6 Ä for CP, Br", and I -, respectively, with hydration numbers of about six, (iv) water molecules approach Li + with their dipole axis, while the X -ion with their O-H bond axis.…”
Section: Introductionmentioning
confidence: 99%
“…The MD simulations with the ST2 model for water indicate a preference of the lone pair orbital orientation not only for Cs + , but also for Li + [5] and Na + [1], The neutron diffraction studies lead for Cs + [25] and for Li + [28] to the same conclusion. The MD simulations with the Central Force model for water indicate for Na + [4] and Mg ++ [6] a preference for trigonal orientation as well as the MC studies of Li + , Na + and K + , where pair potentials based on ab initio calculations are employed (Fig.…”
Section: B) Orientation Of the Water Moleculesmentioning
confidence: 78%
“…The hydration structures of ions in aqueous salt solutions were extensively studied by neutron diffraction [6,8,[66][67][68][69], Xray scattering [70][71][72][73], extended X-ray absorption fine structure spectroscopy [74], and X-ray diffraction [75]. The electronic structures of hydration shells in aqueous salt solutions were studied by photoelectron spectroscopy [76] and X-ray emission spectroscopy [77].…”
Section: Alkali Halide Solutionmentioning
confidence: 99%
“…In order to observe the hydration shell of cations more clearly, we have extracted the contribution of hydrated water molecules with cations from the O K-edge XAS spectra. The coordination numbers of water molecules with cations are referred from the neutron diffraction studies [6,8], in which those of the Li + , Na + , and K + ions are 4, 5, and 6, respectively. The amount of bulk liquid water is estimated by subtracting the water molecules coordinated with cations from total amount of water molecules in aqueous salt solutions.…”
Section: Alkali Halide Solutionmentioning
confidence: 99%
See 1 more Smart Citation